Answer:
Step-by-step explanation:
Simplifying
3x + 2y = 12
Solving
3x + 2y = 12
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2y' to each side of the equation.
3x + 2y + -2y = 12 + -2y
Combine like terms: 2y + -2y = 0
3x + 0 = 12 + -2y
3x = 12 + -2y
Divide each side by '3'.
x = 4 + -0.6666666667y
Simplifying
x = 4 + -0.6666666667y
Simplifying
3x + -3y = 3
Solving
3x + -3y = 3
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3y' to each side of the equation.
3x + -3y + 3y = 3 + 3y
Combine like terms: -3y + 3y = 0
3x + 0 = 3 + 3y
3x = 3 + 3y
Divide each side by '3'.
x = 1 + y
Simplifying
x = 1 + y